Autodesk Revit 2022 architecture - Hamad, Munir M. (Mercury Learning and Information, 2021)
"Covering all of the major techniques, this book uses both metric and imperial units to illustrate the myriad drawing and editing tools for this popular application. Use the companion files to set up drawing exercises and projects and to see all of the book's figures. Autodesk Revit 2022 Architecture includes over 50 "mini-workshops" that complete small projects from concept through actual plotting. Solving all of these workshops will help to master Revit Architecture from beginning to end, without overlooking any of the basic commands and functions. FEATURES: Uses both metric and imperial units to illustrate the myriad drawing and editing tools of this popular applicationIncludes over 50 "mini-workshops" and hundreds of figures that complete small projectsHelps you to prepare for the Revit Architecture Certified Professional examExercises and projects included for use as a textbook"--Publisher's description
Includes index.
Keywords: Autodesk Revit.; Autodesk Revit; Architectural drawing -- Computer-aided design.; Architectural design -- Data processing.; elektronické knihy; electronic books